Civic crowdfunding research: Challenges, opportunities, and future agenda. (February 2015) - Stiver, Alexandra; Barroca, Leonor; Minocha, Shailey; Richards, Mike; Roberts, Dave
Civic crowdfunding is a sub-type of crowdfunding through which citizens, in collaboration with government, fund projects providing a community service. Although in the early stages of development, civic crowdfunding is a promising area for both research and application due to its potential impact on citizen engagement, as well as its influence on the success of a wide range of civic projects ranging from physical structures to amenities and local services. However, the field remains under-addressed in academic research and underdeveloped in terms of the number of civic projects posted to crowdfunding platforms. Acknowledging these issues, we outline the history of civic crowdfunding and describe the current landscape, focusing on online crowdfunding platforms established specifically for the funding of civic projects (Citizinvestor, ioby, Neighbor.ly, Spacehive). The challenges and the opportunities of civic crowdfunding are examined, and its distinguishing characteristics are outlined, including a consideration of the impact of social media and platform features. We then propose a research agenda to help shape the future of this emergent field.